On Economics: A Review of Why Nations Fail by D. Acemoglu and J. Robinson and Pillars of Prosperity by T. Besley and T. Persson - MacLeod, W. Bentley (Journal of Economic Literature, 2013)
The purpose of this essay is to review the books Why Nations Fail by Daron Acemoglu and James Robinson, and Pillars of Prosperity by Timothy Besley and Torsten Persson. The essay briefly discusses the main contributions of the books and the role of politics for economic performance. The review then discusses these contributions in the light of recent research on organizational economics, particularly the modern theory of the firm. (JEL D23, D72, O10, O47, O57)